Comparing ataxias with oculomotor apraxia: a multimodal study of AOA1, AOA2 and AT focusing on video-oculography and alpha-fetoprotein. Issue 1 (December 2017) - Mariani, L.; Rivaud-Péchoux, S.; Charles, P.; Ewenczyk, C.; Meneret, A.; Monga, B.; Fleury, M.-C.; Hainque, E.; Maisonobe, T.; Degos, B.; Echaniz-Laguna, A.; Renaud, M.; et al.
Abstract Whether the recessive ataxias, Ataxia with oculomotor apraxia type 1 (AOA1) and 2 (AOA2) and Ataxia telangiectasia (AT), can be distinguished by video-oculography and alpha-fetoprotein level remains unknown. We compared 40 patients with AOA1, AOA2 and AT, consecutively referred between 2008 and 2015 with 17 healthy subjects. Video-oculography revealed constant impairments in patients such as cerebellar signs, altered fixation, impaired pursuit, hypometric saccades and abnormal antisaccades. Horizontal saccade latencies could be highly increased reflecting oculomotor apraxia in one third of patients. Specific distinctive alpha-fetoprotein thresholds were determined for AOA1 (7–15 µg/L), AOA2 (15–65 µg/L) and AT (>65 µg/L). Early age onset, severe walking disability, movement disorders, sensori-motor neuropathy and cerebellar atrophy were all shared. In conclusion, alpha-fetoprotein level seems to permit a distinction while video-oculography does not and therefore is not mandatory, even if an appropriate oculomotor examination remains crucial. Our findings are that AOA1, AOA2 and AT form a particular group characterized by ataxia with complex oculomotor disturbances and elevated AFP for which the final diagnosis is relying on genetic analysis. These findings could guide genetic analysis, assist reverse-phenotyping and provide background for the interpretation of the numerous variants of unknown significance provided by next-generation sequencing.